Mitigating Academic Risk among Agribusiness Students through the Integration of a Cognitive Socioneuroscience Approach: The Case of the Fun Accounting Double Entry Table at Universitas Jenderal Soedirman - Situmorang, Sawitania; Wijayanti, Irene Kartika Eka; Satriani, Ratna; Solekan, Muhamad (Pascasarjana Universitas Mataram, 2025)
This community service initiative addresses the high academic risk in double-entry bookkeeping comprehension among agribusiness students at Universitas Jenderal Soedirman through the implementation of the Fun Accounting Double Entry Table—a certified HKI educational tool based on cognitive socioneuroscience principles. A structured socialization program engaged 94 students (50 from diploma and, 44 from undergraduate), including activities such as guided practice and independent application using HOTS question on 25 minutes assessment quiz. Facility Index (FI) analysis of the pre-test and post-test assessments evaluated question’s difficulty, while qualitative testimonials captured user feedback. The result is: average scores increased by 48.7% (D3) and 42.6% (S1), systematic journaling mistakes decreased by 84%, 89% of participants reported reduced learning anxiety, and 100% of attendees endorsed table integration into curricula.